THE CORRELATIN OF MOTIVATION TO READINESS TO BE A VOLUNTEER FOR COVID-19 IN NURSING STUDENTS - Rotua Suriany Simamora; Nadhif Dzaki Alwan (Health Media, 2021)
The decrease in motivation of a volunteer can usually also be transmitted to other volunteers, so that if this continues, the problems in the world of volunteering will gradually hamper the movement of voluntary organizations or be passive. This is to find out the motivation of nursing students who are ready to become covid-19 volunteers. This study used an Analytical Observational design with a cross sectional design. Sampling using non-probability sampling type random sampling with a total of 194 respondents. The results showed (P value 0.00 <alpha value 0.05). Shows a relationship between motivation and readiness to volunteer covid19 in nursing students. Motivation with readiness to become a covid-19 volunteer is related to nursing students. To increase the degree of quality of education for student motivation issues and increase readiness to become a covid-19 volunteer by means of a campus that can provide high motivation and training for covid-19 volunteers to students.